Functional Aesthetic Occlusal Plane (FAOP) - Carlos Alexandre Câmara; Renato Parsekian Martins
ABSTRACT Introduction: A reasonable exposure of incisors and gingival tissues is generally considered more attractive than excess or lack of exposure. A reasonable gingival exposure is considered to be around 0 to 2 mm when smiling and 2-4 mm exposure of the maxillary incisor edge when the lips are at rest. Objective: The aim of this paper is to present the Functional Aesthetic Occlusal Plane (FAOP), which aims to help in the diagnosis of the relationships established among molars, incisors and the upper lip. Conclusion: FAOP can complement an existing and established orthodontic treatment plan, facilitating the visualization of functional and aesthetic demands by giving a greater focus on the position of incisors in the relationship established among the incisors, molars and the upper lip stomion.